Teaching Strategy Theory for Effective Classroom Setting - Mallillin, Leovigildo Lito (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study investigates the impact of various teaching strategy theories on establishing an effective classroom environment, specifically focusing on seven key dimensions: visualization, cooperative learning, inquiry-based instruction, differentiation, classroom technology, behavior management, and professional development. Adopting a descriptive quantitative research design, the study surveyed 150 respondents to evaluate the efficacy of these strategies. The results indicate that deliberate practice and the strategic enhancement of teaching methods significantly bolster the learning process. Specifically, the findings highlight that effective strategies foster student self-esteem and confidence by encouraging active verbal engagement and responsiveness to peer ideas. Furthermore, the data supports the integration of inquiry-based instruction as a vital approach to achieving learning objectives and provides teachers with high-impact tools for lesson delivery. The study also emphasizes the necessity of incorporating classroom technology and digital media to actively engage students, alongside behavior management techniques that transform classroom activities into engaging and stimulating experiences. Finally, the results demonstrate the value of professional development and reflective practice, enabling educators to adapt to modern educational trends and competencies. Correlation analysis reveals a significant relationship between the application of teaching strategy theories and the overall effectiveness of the classroom setting as perceived by the respondents.